Porous permanently polarized hydroxyapatite, process for its production and use thereof - Patents.com

JP2025504853APending Publication Date: 2025-02-19UNIV POLITECNICA DE CATALUNYA +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024543046
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-19
Filing Date
2023-01-16
Publication Date
2025-02-19

Smart Images

  • Figure 2025504853000001_ABST
    Figure 2025504853000001_ABST
Patent Text Reader

Abstract

The present invention relates to a porous permanently polarized hydroxyapatite having an average pore diameter of 10 nm to 10,000 nm.Furthermore, the present invention relates to a process for obtaining the porous permanently polarized hydroxyapatite, a composition or material comprising the porous permanently polarized hydroxyapatite, the use of the porous permanently polarized hydroxyapatite or the composition or material as a catalyst, and a composition for preparing the porous permanently polarized hydroxyapatite.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous permanently polarized hydroxyapatite, a process for its production, a composition or material comprising the porous permanently polarized hydroxyapatite, its uses, and a composition for producing the porous permanently polarized hydroxyapatite. [Background technology]

[0002] Scientists are fascinated by the fact that mimicking the morphology of reactors found in nature can dramatically improve catalytic activity. Indeed, confining the volume of chemical reactions to the micro- and nanoscale offers numerous advantages, such as increased surface-to-volume ratios and control of heat and mass transfer, which ultimately translates into improved selectivity and efficiency (Gaitzsch, J.; Huang, X.; Voit, B. Engineering Functional Polymer Capsules towards Smart Nanoreactors. Chem. Rev. 2016, 116, 1053-1093; Rengli, K.; Baumann, P.; Langowska, K.; Onaca, O.; Bruns, N.; Meier, W. Selective and Responsive Nanoreactors. Adv. Funct. Mater. 2011, 21, 1241-1259; Vriezema, DM; Aragones, MC; Elemans, JAAW; Cornelissen, JJLM; Rowan, AE; Nolte, RJM Self-Assembled Nanoreactors.Chem.Rev.2005,105,1445-1489).

[0003] Recent studies have shown that hydroxyapatite (HAp), Ca 10It has been reported that (PO4)6(OH)2 can be used for nitrogen and carbon fixation under mild reaction conditions (Revilla-Lopez, G.; Sans, J.; Casanovas, J.; Bertran, O.; Puiggali, J.; Turon, P.; Aleman, C. Analysis of Nitrogen Fixation by a Catalyst Capable of Transforming N2, CO2 and CH4 into Amino Acids under Mild Reactions Conditions. Appl. Catal. A Gen. 2020, 596, 117526; Sans, J.; Revilla-Lopez, G.; Sanz, V.; Puiggali, J.; Turon, P.; Aleman, C. Permanently Polarized Hydroxyapatite for Selective Electrothermal Catalytic Conversion of Carbon Dioxide into Ethanol. Chem. Commun. 2021, 57, 5163-5166), hydroxyapatite is hypothesized to be a green and inexpensive alternative to traditional catalysts, exhibiting excellent plastic behavior (Sans, J.; Sanz, V.; LJ del Valle; Puiggali, J.; Turon, P.; Aleman, C. Optimization of Permanently Polarized Hydroxyapatite Catalyst. Implications for the Electrophotosynthesis of Amino Acids by Nitrogen and Carbon Fixation. J. Catal. 2021, 397, 98-107).

[0004] The catalytic activation of HAp was developed by subjecting the sintered pellets obtained by compressing HAp powder to a thermally stimulated polarization (TSP) treatment. -The OH- groups are permanently aligned in a specific direction, endowing them with both electrical and electrochemical properties (Sans, J.; Arnau, M.; Turon, P.; Aleman, C. Article OH-. Regulating the Superficial Vacancies and OH- Orientations on Polarized Hydroxyapatite Electrocatalysts. Adv. Mater. Interfaces 2021, in press (DOI: 10.1002 / admi.202100163); Rivas, M.; delValle, LJ; Armelin, E.; Bertran, O.; Turon, P.; Puiggali, J.; Aleman, C. Hydroxyapatite with Permanent Electrical Polarization: Preparation, Characterization, and Response against Inorganic Adsorbates. ChemPhysChem 2018, 19, 1746-1755), but the uniform and dense structure of the catalytic HAp (hereafter referred to as HAp / c) pellets limits the efficiency of the catalyst and therefore the final yield of the reaction.

[0005] Thus, despite the progress already made, there continues to be a need for permanently polarized hydroxyapatites and corresponding compositions that exhibit further optimized catalytic activity. Summary of the Invention [Means for solving the problem]

[0006] In view of the above, therefore, it is an underlying objective of the present invention to make available a composition or material, a process for its manufacture, and uses thereof that adequately address the above needs.

[0007] This object is achieved by a porous permanently polarized hydroxyapatite according to claims 1 and 13, a process for producing a porous permanently polarized hydroxyapatite according to claim 6, a composition or material comprising a porous permanently polarized hydroxyapatite according to claim 14, a use of a porous permanently polarized hydroxyapatite or a composition or material comprising a porous permanently polarized hydroxyapatite according to claim 15, and a composition for preparing a porous permanently polarized hydroxyapatite according to claim 16. Preferred embodiments of the invention are defined in the dependent claims 2 to 5 and 7 to 12. Further preferred embodiments of the invention are defined herein. The subject matter and wording of all claims, respectively, are incorporated herein by express reference.

[0008] According to a first aspect, the present invention relates to a porous, in particular open-pore, permanently polarized hydroxyapatite, ie a permanently polarized hydroxyapatite comprising pores, in particular open pores.

[0009] In principle, the pores of the porous permanently polarized hydroxyapatite may have any shape or morphology, but preferably the pores are in the form of spherical pores.

[0010] Furthermore, the pores of the porous permanently polarized hydroxyapatite may be in the form of interconnected pores, ie pores that exhibit interconnectivity.

[0011] Furthermore, the pores of the porous permanently polarized hydroxyapatite may be present on or at the outer surface of the porous permanently polarized hydroxyapatite, i.e. in the form of superficial pores, and / or may be present on or at the inner surface of the porous permanently polarized hydroxyapatite, or may be part of the inner surface of the porous permanently polarized hydroxyapatite, i.e. in the interior of the porous permanently polarized hydroxyapatite, or in the form of inner pores. Preferably, the porous permanently polarized hydroxyapatite comprises both superficial pores and inner pores.

[0012] Porous permanently polarized hydroxyapatite contains or has an average pore diameter, as measured by electron microscopy (EM) or electron microscopy (EM) techniques, of between 1 nm and 500,000 (five hundred thousand) nm.

[0013] The term "porous permanently polarized hydroxyapatite" as used according to the invention means a porous hydroxyapatite, in particular a synthetic porous hydroxyapatite, which has undergone a complete, in particular almost complete, structural redistribution with a high degree of crystallinity, i.e. in particular a low amount of amorphous calcium phosphate, an increase in electrochemical activity, and the presence of vacancies detected by the accumulation of charge per unit mass and surface. It has an electrochemical activity and ion mobility that does not disappear. Porous permanently polarized hydroxyapatite is as shown in FIG. 1(d): 31 P-NMR spectrum.

[0014] The present invention is based on the surprising finding that the catalytic activity, especially the heterogeneous catalytic activity, of the permanently polarized hydroxyapatite is advantageously enhanced by the presence of pores having the above-mentioned average diameter. Such porosity advantageously results in a suitable wettability of the permanently polarized hydroxyapatite, which is particularly advantageous in terms of improved gas diffusion through the active sites of the permanently polarized hydroxyapatite and the presence of water at the solid-liquid-gas interface. It can therefore advantageously promote the heterogeneous catalytic immobilization of carbon and / or nitrogen, especially from molecular gases. For example, the inventors have been able to demonstrate that the carbon immobilization from carbon dioxide (CO2) and methane (CH4) to obtain ethanol is improved by more than 3000% compared to conventional permanently polarized hydroxyapatite. Similarly, the inventors have been able to demonstrate that the synthesis of ammonia (NH3) by dinitrogen (N2) immobilization is increased by more than 2000%. Therefore, the porous permanently polarized hydroxyapatite according to the present invention shows extraordinary potential for scalability and industrial application for many chemical reactions, in particular enabling a viable green chemistry alternative to heavy metal-based catalysts.

[0015] In an embodiment of the present invention, the above-mentioned average pore diameter, particularly measured by electron microscopy (EM) or electron microscopy (EM) techniques, is 10 nm to 10,000 (ten thousand in words) nm, in particular 50 nm to 1,000 (one thousand in words) nm, preferably 60 nm to 600 nm, more preferably 100 nm to 350 nm. The above-mentioned pore diameters are particularly useful for achieving the above-mentioned advantages of the present invention.

[0016] In a further embodiment of the present invention, the porous permanently polarized hydroxyapatite has nanometer pores and / or submicrometer pores and / or micrometer pores.Preferably, the porous permanently polarized hydroxyapatite has nanometer pores and submicrometer pores, or nanometer pores, submicrometer pores and micrometer pores.Therefore, the selectivity of catalytic reaction can be advantageously improved.In addition, the change from batch process to continuous process can be easily performed if desired due to the improvement of mass transfer.

[0017] The term "nanometric pores" as used according to the present invention means pores having an average diameter of 1 nm to 100 nm, in particular 10 nm to 90 nm, preferably 50 nm to 80 nm, in particular determined by electron microscopy (EM) or electron microscopy (EM) techniques.

[0018] The term "submicrometer pores" as used according to the present invention means pores with an average diameter of more than 100 nm and less than 1000 nm, in particular from 101 nm to 999 nm, in particular from 120 nm to 900 nm, preferably from 150 nm to 200 nm, in particular as determined by electron microscopy (EM) or electron microscopy (EM) techniques.

[0019] The term "micrometric pores" as used according to the present invention means pores having an average diameter of 1 μm to 500 μm, in particular 1 μm to 100 μm or 2 μm to 100 μm, preferably 1 μm to 10 μm, more preferably 5 μm to 10 μm, in particular determined by electron microscopy (EM) or electron microscopy (EM) techniques.

[0020] Advantageously, the additional presence of sub-micrometer pores and / or micrometer pores promotes the catalytic activity of the porous permanently polarized hydroxyapatite.

[0021] In a further embodiment of the invention the nanometric pores have an average pore diameter of 1 nm to 100 nm, in particular 10 nm to 90 nm, preferably 50 nm to 80 nm, in particular determined by electron microscopy (EM) or electron microscopy (EM) techniques.

[0022] In a further embodiment of the invention, the sub-micrometer pores have an average pore diameter of more than 100 nm and less than 1000 nm, in particular from 101 nm to 999 nm, in particular from 120 nm to 900 nm, preferably from 150 nm to 200 nm, in particular determined by electron microscopy (EM) or electron microscopy (EM) techniques.

[0023] In a further embodiment of the invention, the micrometric pores have an average pore diameter of 1 μm to 500 μm, in particular 1 μm to 100 μm, preferably 1 μm to 10 μm, determined in particular by electron microscopy (EM) or electron microscopy (EM) techniques.

[0024] Furthermore, the porous permanently polarized hydroxyapatite may have a porosity of 0.1% to 99%, in particular 5% to 50%, preferably 10% to 35%, determined in particular by calculating the percentage of void space observed by scanning electron microscopy (SEM).

[0025] Furthermore, porous permanently polarized hydroxyapatite has a 1m 2 / g~100m 2 / g, especially 5m 2 / g~80m 2 / g, preferably 10m 2 / g~50m 2 / g specific surface area (SSA).

[0026] In addition, the porous permanently polarized hydroxyapatite is -1 ~150cm -1 , especially 40cm -1 ~120cm -1 , preferably 60cm -1 ~85cm -1 The surface area to volume ratio (sa / vol) may be

[0027] Furthermore, the porous permanently polarized hydroxyapatite may have a crystallinity, in particular determined by wide-angle X-ray scattering (WAXS), of 65% or more, in particular 70% or more, preferably 75% or more, more preferably between 75% and 99.9%.

[0028] Furthermore, the porous permanently polarized hydroxyapatite may comprise crystallites having an average size, preferably an average diameter, of 20 nm to 500 nm, in particular 50 nm to 200 nm, preferably 70 nm to 100 nm, determined in particular by wide-angle X-ray scattering (WAXS) or wide-angle X-ray diffraction (WAXD).

[0029] Furthermore, the porous permanently polarized hydroxyapatite may have a water flow absorption, in particular determined by optical microscopy (in particular equipped with a contact angle goniometer), of 0.1 μL / s to 20 μL / s, in particular 0.2 μL / s to 10 μL / s, preferably 1 μL / s to 6 μL / s.

[0030] In a further embodiment of the invention, the porous permanently polarized hydroxyapatite has a wide-angle X-ray scattering (WAXS) or wide-angle X-ray diffraction (WAXD) pattern as shown in Figure 1(a). The wide-angle X-ray scattering (WAXS) or wide-angle X-ray diffraction (WAXD) pattern exhibits peaks, in particular representative or unique peaks, at 2θ = 25.9°, 31.7°, 32.1°, 32.8°, 34.0° and 39.8°. Preferably, said pattern is performed or obtained at room temperature, preferably at a temperature between 20°C and 25°C, and / or under atmospheric conditions, in particular atmospheric humidity and / or atmospheric pressure.

[0031] The term "room temperature" as used according to the present invention means a temperature between 15°C and 35°C, in particular between 18°C ​​and 30°C, preferably between 20°C and 30°C, more preferably between 20°C and 28°C, in particular between 20°C and 25°C.

[0032] In a further embodiment of the present invention, the porous permanently polarized hydroxyapatite has a Raman spectrum as shown in Figure 1(b). The Raman spectrum has a Raman spectrum of ν1 = 962 cm -1 , ν2=400cm -1 ~480cm -1 , ν3=570cm -1 ~625cm -1 , and ν4=1020cm -1 ~1095cm -1 For hydroxyapatite, the peak at 3574 cm -1 ν-OH at 878cm -1 , 848cm -1 and 794 cm -1 Preferably, said pattern is performed or obtained by recording at room temperature, preferably at a temperature between 20° C. and 25° C., and / or under atmospheric conditions, in particular atmospheric humidity and / or atmospheric pressure, using a laser, in particular at a wavelength of 532 nm.

[0033] In a further embodiment of the present invention, the porous permanently polarized hydroxyapatite is 31P-NMR spectrum, said spectrum exhibiting a characteristic peak at or near 2.6 ppm, i.e. in the range of 2.5 ppm to 2.7 ppm, corresponding to the phosphate groups of hydroxyapatite. Preferably, said spectrum is performed or obtained using solid porous permanently polarized hydroxyapatite at a temperature of 20°C to 25°C and with phosphoric acid (H3PO4) as a reference. Furthermore, said spectrum is preferably obtained or can be obtained using a 400 MHz or 400.1 MHz nuclear magnetic resonance (NMR) spectrometer. In general, depending in particular on the NMR spectrometer used, the porous permanently polarized hydroxyapatite exhibits peaks, in particular characteristic peaks, in the range of 2.3 ppm to 2.9 ppm, in particular 2.4 ppm to 2.8 ppm, preferably 2.5 ppm to 2.7 ppm, more preferably 2.5 ppm to 2.6 ppm, corresponding to the phosphate groups of hydroxyapatite. 31 P-NMR spectrum.

[0034] Furthermore, the porous permanently polarized hydroxyapatite may have a proportion of amorphous calcium phosphate of from greater than 0% to 17% by weight, in particular from greater than 0% to 9% by weight, preferably from greater than 0% to 5% by weight, based on the total weight of the porous permanently polarized hydroxyapatite.

[0035] Additionally, the porous permanently polarized hydroxyapatite may be free of amorphous calcium phosphate.

[0036] Furthermore, the porous permanently polarized hydroxyapatite may have a proportion of tricalcium phosphate, in particular β-tricalcium phosphate, of from more than 0% to 35% by weight, in particular from more than 0% to 12% by weight, preferably from more than 0% to 5% by weight, in particular less than 0.5% by weight, based on the total weight of the porous permanently polarized hydroxyapatite.

[0037] Furthermore, the porous permanently polarized hydroxyapatite may be free of tricalcium phosphate, in particular free of β-tricalcium phosphate.

[0038] In addition, the porous permanently polarized hydroxyapatite was 7 Ωcm 2 ~10 4 Ωcm 2 , especially 10 7 Ωcm 2 ~10 5 Ωcm 2 , preferably 10 5 Ωcm 2 In particular, the bulk resistance may increase (by only) 0.1% to 33%, in particular 4% to 63%, preferably 4% after 3 months. The term "bulk resistance" as used according to the present invention means the resistance to electron transfer and may be measured by electrochemical impedance spectroscopy.

[0039] Furthermore, the porous permanently polarized hydroxyapatite may have a surface capacitance that decreases by less than 8%, in particular less than 5% after 3 months. Preferably, the porous permanently polarized hydroxyapatite may have a surface capacitance that decreases by 0% or more than 0% to 8%, more preferably 0% or more than 0% to 5% after 3 months. The term "surface capacitance" as used according to the present invention means the capacitance due to the surface changes of the hydroxyapatite induced by the thermal polarization process and may be measured by electrochemical impedance spectroscopy.

[0040] Preferably, the porous permanently polarized hydroxyapatite is free of coating, i.e. does not have any coating, so that the blocking of the pores due to the presence of a coating can be advantageously avoided and the pores can exercise their promoting influence on the catalytic activity of the porous permanently polarized hydroxyapatite without any loss.

[0041] Alternatively, the porous permanently polarized hydroxyapatite may have or include a coating.

[0042] Furthermore, the porous permanently polarized hydroxyapatite may be in the form of particles, which may have a diameter, preferably an average diameter, of 10 nm to 5,000 (literally five thousand) nm, in particular 100 nm to 1,000 (literally one thousand) nm, preferably 100 nm to 300 nm, in particular determined by electron microscopy (EM) or electron microscopy (EM) techniques.

[0043] Furthermore, the porous permanently polarized hydroxyapatite may be in the form of a powder, in particular having the particles mentioned in the previous paragraph.

[0044] Furthermore, the porous permanently polarized hydroxyapatite may be in the form of a shaped body, which may have a polygonal, for example triangular, quadrangular or rectangular, pentagonal, hexagonal, heptagonal, octagonal or nonagonal cross section, or a cross section without corners, in particular circular, oval or elliptical.

[0045] In particular, the shaped body may be in the form of a disk, a plate, a cone or a cylinder.

[0046] Furthermore, the shaped body may have a thickness of, for example, from greater than 0 cm to 10 cm, in particular from greater than 0 cm to 1 cm, preferably from greater than 0 cm to 0.2 cm.

[0047] Furthermore, the porous permanently polarized hydroxyapatite is preferably in the form of a catalyst, in particular a ceramic catalyst, preferably a bioceramic catalyst.

[0048] According to a second aspect, the present invention relates to a process for obtaining or preparing a porous permanently polarized hydroxyapatite, in particular according to the first aspect of the invention, comprising the following steps: (a) providing a mixture comprising or consisting of a hydroxyapatite powder, in particular a crystalline hydroxyapatite powder, and a pore-forming material; (b) molding or modeling the mixture provided in step (a) to obtain a molded body comprising or consisting of the hydroxyapatite powder and the pore-forming material; (c) sintering the body obtained in step (b) to remove the pore-forming material and obtain a body comprising or consisting of porous hydroxyapatite; (d) a constant or variable direct current voltage, especially between 250 V and 2550 V, or an equivalent electric field, especially between 1.49 kV / cm and 15 kV / cm or, In particular, electrostatic discharges of 2500V to 1500000V, or equivalent electric fields of 148.9kV / cm to 8928kV / cm, applying a magnetic field to the molded body obtained in step (c) to obtain a molded body comprising or consisting of porous permanently polarized hydroxyapatite; (e) cooling the molded body obtained in step (d) while maintaining the DC voltage or the equivalent electric field applied in step (d); or, A step of cooling the molded body obtained in the step (d) while maintaining the electrostatic discharge or the equivalent electric field applied in the step (d); or, A step of cooling the molded body obtained in the step (d) without maintaining the DC voltage or the equivalent electric field applied in the step (d); or, and cooling the molded body obtained in step (d) without maintaining the electrostatic discharge or the equivalent electric field applied in step (d).

[0049] The term "pore-forming material" as used according to the present invention means a material or additive capable of forming or leaving pores in, i.e. within, and / or on, i.e. at the surface of, another material, in particular after removal from said material. The pore-forming material according to the present invention may also be referred to as a "pore-forming additive".

[0050] The term "hydroxyapatite powder" as used according to the present invention means a powder that comprises or consists of hydroxyapatite. The hydroxyapatite may be in the form of natural, i.e. naturally occurring, hydroxyapatite and / or in the form of synthetic hydroxyapatite. Furthermore, the hydroxyapatite may be in the form of crystalline hydroxyapatite.

[0051] Preferably, in step (a), the mixture is provided in the form of a homogeneous and / or pasty mixture, in particular in the form of an ink or ink composition.

[0052] Furthermore, the hydroxyapatite powder used in step (a) to provide the mixture may have an average particle size of 10 nm to 5,000 (five thousand) nm, in particular 50 nm to 1,000 (one thousand) nm, preferably 100 nm to 1,000 (one thousand) nm, more preferably 100 nm to 300 nm, in particular as determined by electron microscopy (EM) or electron microscopy (EM) techniques.

[0053] Furthermore, the mixture provided in step (a) preferably has a proportion of hydroxyapatite powder of 1% to 99.9% by weight, in particular 10% to 90% by weight, preferably 20% to 65% by weight, based on the total weight of the mixture.

[0054] Furthermore, the mixture provided in step (a) preferably has a proportion of pore-forming material of 1% to 90% by weight, in particular 10% to 80% by weight, preferably 35% to 65% by weight, based on the total weight of the mixture.

[0055] Advantageously, the pore diameter, in particular the average pore diameter and the porosity of the porous permanently polarized hydroxyapatite may be controlled by the proportion of pore-forming material used to provide the mixture of step (a).

[0056] Furthermore, the mixture provided in step (a) further comprises a liquid, in particular water, which may have a proportion of 10% to 90% by weight, in particular 20% to 80% by weight, preferably 40% to 60% by weight, based on the total weight of the mixture.

[0057] Furthermore, step (a) may be carried out by first adding a portion of the pore-forming material to the hydroxyapatite powder, in particular followed by stirring, and thereafter adding the remaining portion of the pore-forming material to the hydroxyapatite powder, in particular followed by further stirring.

[0058] Furthermore, step (a) may be carried out at a temperature between −10° C. and 250° C., in particular between −5° C. and 100° C., preferably between 0° C. and 25° C. The temperature ranges disclosed in this paragraph are particularly useful for providing a mixture exhibiting good rheological conditions, which are advantageous for carrying out step (b).

[0059] Furthermore, the process may comprise a further step (ab) between step (a) and step (b) of aging the mixture, i.e. storing the mixture. In this way, a homogeneous distribution of the pore-forming material in the mixture can be advantageously ensured. Step (ab) may be carried out at a temperature between -10°C and 250°C, in particular between -5°C and 100°C, preferably between 0°C and 25°C. Furthermore, step (ab) may be carried out for a time between 1 minute and 96 hours, in particular between 1 minute and 24 hours, preferably between 1 minute and 12 hours, for example for 6 hours.

[0060] Additionally, the hydroxyapatite powder used in step (a) may be prepared by using diammonium phosphate (diammonium hydrogen phosphate, (NH4)2HPO4) and calcium nitrate (Ca(NO3)2) as reactants or starting materials. In particular, the hydroxyapatite powder may be prepared by using: (a 01 ) providing a mixture of diammonium phosphate and calcium nitrate, in particular an aqueous mixture, preferably an aqueous-alcoholic mixture; (a 02 ) process (a 01stirring the mixture provided in step (a), in particular at room temperature; (a 03 ) process (a 02 subjecting the stirred mixture to hot water treatment; (a 04 ) process (a 03 cooling the hydrothermally treated mixture; (a 05 ) process (a 04 and separating the precipitate obtained after cooling the mixture of (a 06 ) process (a 05 and freeze-drying the precipitate separated by (a) to produce hydroxyapatite, particularly crystalline hydroxyapatite.

[0061] Process (a 01 ) may in particular be carried out by using a mixture comprising or consisting of diammonium phosphate, calcium nitrate, water, in particular deionized water, ethanol and, optionally, a chelated calcium solution. Advantageously, the pH value of the mixture and / or the pH value of the aqueous calcium nitrate solution applied to provide the mixture may be adjusted to between 10 and 12, preferably to 11. In this way, the shape and size of the hydroxyapatite, in particular in the form of nanoparticles, may be controlled. Furthermore, step (a 02 ) may be carried out under stirring, particularly under gentle stirring, for example at 150 rpm to 400 rpm. 02 According to the present invention, step (a) can be carried out for 1 minute to 12 hours, in particular for 1 hour. 02 ) may be referred to as an aging step. 03 ) may be carried out at a temperature of 60°C to 240°C, preferably 150°C. 03 ) may be carried out at a pressure of 1 bar to 250 bar, preferably 20 bar. 03 The step (a) may be carried out for 0.1 to 72 hours, preferably 24 hours. 04 ) is the process (a 03The mixture treated with hot water in step (a) may be cooled to a temperature of 0° C. to 90° C., particularly 25° C. 05 ) may be carried out by centrifugation and / or filtration. 05 The precipitate separated in step (a 06 Before carrying out step (a), the mixture may be washed, in particular with water and / or a mixture of ethanol and water. 06 ) may be carried out for 1 to 4 days, particularly 2 to 3 days, and preferably 3 days.

[0062] Furthermore, step (b) is preferably carried out by extrusion, in particular robotic extrusion, i.e. robot-assisted extrusion.

[0063] More preferably, step (b) is carried out by 3D printing or additive manufacturing, in particular robotic 3D printing or additive manufacturing, i.e. robot-assisted 3D printing or additive manufacturing.

[0064] Furthermore, step (b) may be carried out at a temperature of -10°C to 250°C, particularly -5°C to 100°C, and preferably 0°C to 25°C.

[0065] Furthermore, step (c) is preferably carried out at a temperature of 700°C to 1200°C, in particular 700°C to 1150°C, preferably 800°C to 1100°C, in particular 1000°C.

[0066] Furthermore, the process preferably comprises, between steps (c) and (d), - a further step (cd) of pressing the shaped body obtained in step (c) to obtain a pressed shaped body.

[0067] In particular, step (cd) may be carried out at a pressure of 1 MPa to 1000 MPa, in particular 100 MPa to 800 MPa, preferably 600 MPa to 700 MPa. Furthermore, step (cd) may be carried out for 1 to 90 minutes, in particular 5 to 50 minutes, preferably 10 to 30 minutes.

[0068] The pressed body may have a polygonal, for example triangular, quadrangular or rectangular, pentagonal, hexagonal, heptagonal, octagonal or nonagonal cross section, or may have no corners, in particular a circular, oval or elliptical cross section. Furthermore, the pressed body may have a thickness of, for example, more than 0 cm to 10 cm, in particular more than 0 cm to 5 cm, preferably more than 0 cm to 2 cm. In particular, the pressed body may have a thickness of 0.1 cm to 10 cm, in particular 0.1 cm to 5 cm, preferably 0.5 cm to 2 cm.

[0069] In particular, the pressed body may be in the form of a disk, a plate, a cone or a cylinder.

[0070] Advantageously, by carrying out step (d), catalytic activation of the shaped body or the porous hydroxyapatite obtained in step (c) can be achieved. Preferably, step (d) is carried out by placing the shaped body obtained in step (c) between a positive electrode and a negative electrode, preferably the shaped body obtained in step (c) is in contact with both electrodes, i.e. the positive electrode and the negative electrode. The electrodes may be, by way of example, in the form of stainless steel plates, in particular stainless steel AISI 304 plates. Furthermore, the electrodes may have a mutual spacing of 0.01 mm to 10 cm, in particular 0.01 mm to 5 cm, preferably 0.01 mm to 1 mm.

[0071] Moreover, the electrode may have various shapes. The electrode may have a polygonal cross section, for example a square or a rectangle, or a cross section without corners, in particular a circular, oval or elliptical cross section. In particular, the electrode may have a thickness of, for example, more than 0 cm to 10 cm, in particular more than 0 cm to 5 cm, preferably more than 0 cm to 1 mm. For example, the electrode may be in the form of a disk, a plate or a cylinder.

[0072] Furthermore, the constant or variable DC voltage or equivalent electric field may be applied in the above step (d) for 1 hour to 24 hours, particularly 0.1 hour to 10 hours, and particularly 1 hour.

[0073] Furthermore, the DC voltage applied in the above step (d) is preferably 500 V, which corresponds to a constant electric field of 3 kV / cm.

[0074] Furthermore, the equivalent electric field applied in the above step (d) is preferably 3 kV / cm.

[0075] Furthermore, step (d) is preferably carried out at a temperature of at least 900° C., more preferably at least 1000° C. Preferably, step (d) is carried out at a temperature of 900° C. to 1200° C., in particular 1000° C. to 1200° C., especially 1000° C.

[0076] Furthermore, step (d) may preferably be carried out for a period of from greater than 0 minutes to 24 hours, or for at least 1 minute.

[0077] Preferably, step (d) is carried out by applying a constant or variable DC voltage of 500 V at 1000° C. for 1 hour to the compact obtained in step (c).

[0078] Furthermore, the above step (e) may be carried out by cooling the molded body obtained in step (d) to room temperature.

[0079] Furthermore, the above step (e) may be carried out for 1 minute to 72 hours, particularly 15 minutes to 5 hours, and preferably 15 minutes to 2 hours.

[0080] In a further embodiment of the invention, the pore-forming material comprises or is a polymer, in particular a synthetic polymer, ie a polymer produced in a laboratory, or a biopolymer, ie a polymer occurring in nature.

[0081] In a further embodiment of the invention the polymer is selected from the group consisting of poloxamers, polyolefins, polyesters, polyamides, polyimides, polyvinyl alcohols, polyurethanes, polycarbonates, polyalkyl terephthalates, polyaryl terephthalates, polyaryl ether ketones, polyhydroxyalkanoates, proteins, such as extracellular proteins and / or globular proteins and / or enzymes and / or antibodies and / or blood clotting factors, polysaccharides and mixtures of at least two of the above mentioned polymers.

[0082] In a further embodiment of the invention, the polymer is a poloxamer. Poloxamers are non-ionic triblock copolymers that contain or consist of a central hydrophobic chain of polyoxypropylene (poly(propylene oxide)) flanked by two hydrophilic chains of polyoxyethylene (poly(ethylene oxide)). Poloxamers are also known under the trade names Pluronic, Kolliphor (pharmaceutical grade) and Synperonic. For the generic name poloxamer, these copolymers are generally named with the letter P (for poloxamer) followed by three digits: the first two digits multiplied by 100 give the molecular weight or approximate molecular weight of the polyoxypropylene core, i.e., the central hydrophobic chain of polyoxypropylene, and the last digit multiplied by 10 gives the polyoxyethylene content (e.g., P407=poloxamer with a polyoxypropylene molecular weight of 4000 g / mol and a polyoxyethylene content of 70%). In the Pluronic and Synperonic trademarks, the coding of these copolymers begins with a letter that defines their physical form at room temperature (L = liquid, P = paste, F = flake (solid)), followed by two or three digits. The first digit (two digits in the case of three digits) of the numerical designation multiplied by 300 indicates the approximate molecular weight of the polyoxypropylene core, and the last digit multiplied by 10 indicates the polyoxyethylene content (for example, L61 indicates a polyoxypropylene molecular weight of 1,800 g / mol and a polyoxyethylene content of 10%). In the given example, Poloxamer 181 (P181) is equivalent to Pluronic L61 and Synperonic PE / L61.

[0083] Surprisingly, it has been found that poloxamer in particular can 1) precisely control the final structure and porosity of the porous permanently polarized hydroxyapatite without affecting its crystalline structure, and 2) can be removed by the sintering step (c) without affecting the dimensional and mechanical stability of the final porous permanently polarized hydroxyapatite.

[0084] In a further embodiment of the invention, the poloxamer comprises a polyoxypropylene core, i.e. a central hydrophobic chain of polyoxypropylene or central polyoxypropylene unit, having a molecular weight of 1 g / mol to 500,000 (literally five hundred thousand) g / mol, in particular 1,000 (literally one thousand) g / mol to 30,000 (literally thirty thousand) g / mol, preferably 10,000 (literally ten thousand) g / mol to 20,000 (literally twenty thousand) g / mol.

[0085] Preferably, the poloxamer has a polyoxypropylene content, ie a proportion of polyoxypropylene, between 1% and 90% by weight, in particular between 10% and 80% by weight, preferably between 35% and 65% by weight.

[0086] In a further embodiment of the invention, the poloxamer has a polyoxyethylene content, i.e. a proportion of polyoxyethylene, of 1% to 90% by weight, in particular 10% to 80% by weight, preferably 35% to 65% by weight.

[0087] In a further embodiment of the invention, the polymer has a proportion of 1% to 90% by weight, in particular 10% to 80% by weight, preferably 20% to 80% by weight, more preferably 35% to 65% by weight, based on the total weight of the pore-forming material. For example, the polymer may have a proportion of 50%, 60%, 73% or 78% by weight, based on the total weight of the pore-forming material.

[0088] In particular, the polymer may have a proportion of 50% by weight or less, in particular 20% by weight to 50% by weight, preferably 35% by weight to 50% by weight, based on the total weight of the pore-forming material. Surprisingly, it has been found that the proportion of polymer disclosed in this paragraph leads to the formation of nanometer pores and submicrometer pores, in particular the formation of only nanometer pores and submicrometer pores, preferably the formation of only nanometer pores. Thus, by adjusting the proportion of polymer, the formation of submicrometer pores and / or micrometer pores can be avoided.

[0089] Alternatively, the polymer may in particular have a proportion of 50% by weight or more, in particular more than 50% by weight, preferably 60% to 90% by weight, more preferably 60% to 80% by weight, based on the total weight of the pore-forming material. Surprisingly, it has been found that the proportion of polymer disclosed in this paragraph leads not only to the formation of nanometer pores and submicrometer pores, but also to the formation of micrometer pores. Thus, the catalyst surface area may be advantageously increased. Moreover, the further formation of submicrometer pores and micrometer pores may facilitate a continuous process by improving mass transfer.

[0090] Moreover, the proportions of polymers disclosed in the preceding paragraphs have the (additional) advantage that the moulded bodies obtained in step (c) in particular retain the desired shape without exhibiting observable cracks or shrinkage and have good structural stability.

[0091] Furthermore, the pore-forming material may preferably comprise a liquid, in particular water, more specifically the liquid, in particular water, may preferably have a proportion of 10% to 90% by weight, in particular 20% to 80% by weight, preferably 40% to 60% by weight, based on the total weight of the pore-forming material.

[0092] In a further embodiment of the invention, the pore-forming material is in the form of a gel, preferably a hydrogel, ie a water-containing gel.

[0093] According to a third aspect, the present invention relates to a porous permanently polarized hydroxyapatite obtained or obtainable by a process according to the second aspect of the invention.

[0094] For further features and advantages of the porous permanently polarized hydroxyapatite and the process for obtaining the same, reference is made generally to the above description, i.e. the disclosure given under the first and second aspects of the invention. The features and advantages mentioned in the above description with respect to the porous permanently polarized hydroxyapatite and the process for obtaining the same also apply mutatis mutandis with respect to the porous permanently polarized hydroxyapatite according to the third aspect of the invention.

[0095] According to a fourth aspect, the present invention relates to a composition or material comprising or consisting of a porous permanently polarized hydroxyapatite according to the first or third aspect of the invention.

[0096] Preferably, the composition or material is in the form of a catalyst, in particular a ceramic catalyst, preferably a bioceramic catalyst.

[0097] Furthermore, the porous permanently polarized hydroxyapatite may have a proportion of 1% to 99.9% by weight, in particular 10% to 90% by weight, preferably 20% to 65% by weight, based on the total weight of the composition or material.

[0098] The composition or material may further comprise an active ingredient. The active ingredient may in particular be a biological or pharmaceutical active ingredient. The active ingredient may in particular be selected from the group consisting of antibacterial ingredients, more particularly antibiotic ingredients, wound healing promoting ingredients, bactericidal ingredients, anti-inflammatory ingredients, blood coagulation promoting ingredients, growth factors, cell differentiation factors, cell adhesion factors, cell recruitment factors, cell receptors, cell binding factors, cytokines, peptides, structural proteins, extracellular proteins such as collagen, serum proteins such as albumin, polysaccharides such as hyaluronic acid, oligonucleotides, polynucleotides, DNA, RNA, salts thereof, stereoisomers thereof, more particularly diastereomers thereof, and mixtures thereof.

[0099] For example, the active ingredient may be selected from the group consisting of biguanides, polyhexamethylene biguanide (PHMB), triclosan, chlorhexidine, gentamicin, vitamins, copper, zinc, silver, gold, and mixtures thereof.

[0100] The composition or material may further comprise a material selected from the group consisting of a polymer, a ceramic, a silicate, an organometallic compound, and mixtures thereof.

[0101] The polymer may be a biodegradable polymer, i.e. a polymer that degrades in vivo, i.e. in the human or animal body, or a non-biodegradable polymer. Furthermore, the polymer may be a biopolymer, i.e. a naturally occurring polymer, or a synthetic polymer, i.e. a technical or non-naturally occurring polymer. Furthermore, the polymer may be a homopolymer or a copolymer, i.e. a polymer that comprises at least two, in particular only two, or more different monomer units.

[0102] The polymers may in particular be selected from the group consisting of polyolefins, polyesters, polyamides, polyimides, polyvinyl alcohols, polyurethanes, polycarbonates, polyalkyl terephthalates, polyaryl terephthalates, polyaryl ether ketones, polyhydroxyalkanoates, proteins, such as extracellular proteins and / or globular proteins and / or enzymes and / or antibodies and / or blood clotting factors, polysaccharides, and mixtures thereof.

[0103] In particular, the polymers are polyethylene, low density polyethylene, high density polyethylene, high molecular weight polyethylene, ultra-high molecular weight polyethylene, polypropylene, polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polyamide 6, polyamide 6, polyamide 6-6, polyamide 6-12, polyamide 12, rayon, silk, in particular spider silk, polytetrafluoroethylene, polyvinylidene dichloride, polyvinylidene fluoride, polytetrafluoropropylene, polyhexafluoropropylene, polyvinyl alcohol, polyglycolide, polylactide, polydioxanone, polyhydroxybutyrate, poly-3-hydroxybutyrate, poly-4-hydroxybutyrate, polytrimethylene carbonate, poly-ε -caprolactone, collagen, gelatin, elastin, reticulin, fibronectin, laminin, fibrin, fibrinogen, albumin, starch, amylose, amylopectin, dextran, dextrin, cellulose, cellulose derivatives such as alkylcellulose, methylcellulose, hydroxyalkylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, carboxyalkylcellulose, carboxymethylcellulose, chitin, chitosan, hyaluronic acid, dextran sulfate, heparin, heparan sulfate, chondroitin sulfate, dermatan sulfate, DNA, RNA, salts thereof, stereoisomers thereof, copolymers thereof, and mixtures thereof.

[0104] The composition or material may further comprise an inorganic catalyst, in particular an inorganic photocatalyst. More specifically, the composition or material may be at least partially, in particular only partially, or completely coated with an inorganic catalyst, in particular a photocatalyst. The inorganic catalyst may be a catalyst such as TiO2, MgO2, MnO2, or a combination thereof.

[0105] Further, the composition or material is preferably free of a coating, i.e., the composition or material is preferably free of any coating.

[0106] Alternatively, the composition or material may have or include a coating. In particular, the composition or material may be at least partially, in particular only partially or completely coated with aminotris(methylene phosphonic acid) and / or zirconium oxychloride (ZrOCl2) and / or zirconia (ZrO2). More specifically, the composition or material may have a three-layer coating, in particular the three-layer coating may consist of two layers of aminotris(methylene phosphonic acid) and a layer of zirconium oxychloride (ZrOCl2) or zirconia (ZrO2), preferably the layer of zirconium oxychloride is disposed or sandwiched between two layers of aminotris(methylene phosphonic acid).

[0107] Furthermore, the composition or material may preferably be for medical use, in particular a pharmaceutical composition or material.

[0108] Furthermore, the composition or material may preferably be a medical device, in particular an implant, such as a bone implant or a prosthesis, in particular a knee prosthesis or a hip prosthesis.

[0109] For further features and advantages of the composition or material, reference is made generally to the above description, i.e. the disclosure given under the first, second and third aspects of the invention. The features and advantages described in the above description in particular with respect to the porous permanently polarized hydroxyapatite also apply mutatis mutandis with respect to the composition or material according to the fourth aspect of the invention.

[0110] According to a fifth aspect, the present invention relates to the use of a porous permanently polarized hydroxyapatite according to the first or third aspect of the invention, or of a composition or material according to the fourth aspect of the invention, as a catalyst, in particular in reactions for the synthesis or preparation of organic molecules, preferably ethanol, or in reactions for the synthesis or preparation of inorganic molecules, preferably ammonia.

[0111] Particularly preferably, the porous permanently polarised hydroxyapatite according to the first or third aspect of the invention or the composition or material according to the fourth aspect of the invention is used as a catalyst for the synthesis or preparation of ethanol or ammonia.

[0112] For further features and advantages of the use, reference is made generally to the above description, i.e. the disclosure given under the first, second, third and fourth aspects of the invention. The features and advantages described in the above description with respect to the porous permanently polarized hydroxyapatite also apply mutatis mutandis with respect to the use according to the fifth aspect of the invention.

[0113] According to a sixth aspect, the present invention relates to a composition, in particular a paste or ink composition, preferably a 3D printing ink, for obtaining or preparing a porous permanently polarized hydroxyapatite, in particular according to the first or third aspect of the invention, which composition comprises or consists of a hydroxyapatite powder and a pore-forming material.

[0114] Preferably, the hydroxyapatite powder has an average particle size of 10 nm to 5,000 (five thousand) nm, in particular 50 nm to 1,000 (one thousand) nm, preferably 100 nm to 1,000 (one thousand) nm, more preferably 100 nm to 300 nm, in particular determined by electron microscopy (EM) or electron microscopy (EM) techniques.

[0115] Furthermore, the hydroxyapatite powder preferably has a proportion of 1% to 99.9% by weight, in particular 10% to 90% by weight, preferably 20% to 65% by weight, based on the total weight of the composition.

[0116] Furthermore, the pore-forming material preferably has a proportion of 1% to 90% by weight, in particular 10% to 80% by weight, preferably 35% to 65% by weight, based on the total weight of the composition.

[0117] Furthermore, the composition preferably comprises a liquid, in particular water, which may in particular have a proportion of 10% to 90% by weight, in particular 20% to 80% by weight, preferably 40% to 60% by weight, based on the total weight of the composition.

[0118] For further features and advantages of the composition, reference is made generally to the above description, i.e. the disclosure given under the first, second, third, fourth and fifth aspects of the invention. The features and advantages described in the above description, in particular with respect to the porous permanently polarized hydroxyapatite and the pore-forming material, also apply mutatis mutandis with respect to the composition according to the sixth aspect of the invention.

[0119] Further features and advantages of the present invention will become apparent from the following drawings, its description and examples, in conjunction with the subject matter of the dependent claims. The individual features can be realized alone or in combination in one embodiment of the present invention. The preferred embodiments are merely for illustrating and better understanding the present invention, and are not to be understood as limiting the present invention in any way. [Brief description of the drawings]

[0120] [Figure 1] Structural characterization of the as-prepared HAp, s-HAp and s / 50-HAp samples: (a) WAXD spectrum, (b) Raman spectrum in the region of the four characteristic vibrational modes (ν1–ν4), (c) stacked Raman spectrum of the samples in the region of 3550–3600 cm−1 corresponding to the ν(OH) vibrational mode. [Diagram 2] SEM micrographs of s-HAp and s / x-HAp samples obtained with different Pluronic hydrogel mass percentages. Porosity was clearly observed when hydrogel was introduced into the blend. [Diagram 3] Dependence of (a) pore size and (b) porosity of s / x-HAp samples on the weight percent of Pluronic hydrogel. [Figure 4](a) Syringe-extruded HAp ink loaded with 60 wt% Pluronic hydrogel. (b) Effect of sintering on the structure of the same HAp ink modeled with different geometries. (c) SEM examination of the external (c1) and internal (c2) porosity of the HAp ink. [Diagram 5] Geometric comparison of (a) 60-HAp / c cube and (b) HAp / c disk. [Figure 6] (a) Comparison of ethanol yields obtained from CO2 and CH4 fixation reactions catalyzed by HAp / c and 60-HAp / c. The reactions were carried out with an initial CO2:CH4 mixture (3 bar each), 1 mL of water, and at 140 °C for 48 h without UV irradiation. (b) Change in ethanol production as a function of initial water content (expressed in mmol / gcat instead of μmol / gcat). The remaining reaction conditions were identical to (a). [Figure 7] (a) Comparison of ammonium yields obtained from N2 fixation reactions catalyzed by HAp / c and 60-HAp / c. The reactions were carried out at 120 °C with UV irradiation for 24 h using 20 mL of water with initial N2 pressure (6 bar). [Figure 8] Pore ​​size distribution histogram of s / x-HAp samples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0121] Experimental Section 1.Material Calcium nitrate Ca(NO3)2, diammonium hydrogen phosphate [(NH4)2HPO4; purity >99.0%], ammonium hydroxide 30% in water [NH4OH; purity: 28-30% w / w], zirconyl chloride (ZrOCl2·8H2O; ZC), aminotris(methylenephosphonic acid) (ATMP) and initial Pluronic® F-127 polymer (C3H6O·C2H4O). x , BioReagent powder) were purchased from Sigma Aldrich. Ethanol (>99.5% purity) was purchased from Scharlab. N2, CH4 and CO2 gases, >99.995% purity, were purchased from Messer. All experiments were performed in Milli-Q water.

[0122] 2. Synthesis of hydroxyapatite (HAp) 15 mL of 0.5 M (NH4)2HPO4 in deionized water were added at a rate of 2 mL / min to 25 mL of 0.5 M Ca(NO3)2 solution in ethanol, previously adjusted to pH 11 with ammonium hydroxide solution. The mixture was aged for 1 h at room temperature with gentle stirring (150 rpm). A hydrothermal treatment was performed at 150 °C for 24 h using an autoclave Digestec DAB-2. The autoclave was allowed to cool before opening. The precipitate was separated by centrifugation and washed with water and a 60 / 40 v / v mixture of ethanol / water (2 times). After freeze-drying for 3 days, a white powder was obtained.

[0123] 3. Synthesis of Pluronic Hydrogels 25 g of distilled water was mixed with 25 g of Pluronic® F-127 polymer using a FlackTek SpeedMixer at 3500 rpm for 5 minutes. Then, 50 g of Pluronic® polymer was added and stirred vigorously under the same conditions. The resulting hydrogel was stored at 4°C.

[0124] 4. Synthesis of Porous HAp Ink HAp powder (hereafter referred to as prepared HAp) was obtained from hydrothermal route and freeze-dried for 72 h to remove water. Pluronic hydrogel was prepared from a mixture of water and Pluronic® F-127.

[0125] HAp ink with the desired weight percentage of Pluronic hydrogel was obtained by slowly adding half of the weighed Pluronic hydrogel to the HAp powder, followed by vigorous stirring at 2500 rpm for 2 min using a Fisherbrand™ Digital Vortex Mixer. This process was repeated again with the remaining hydrogel to obtain a homogeneous mixture. All procedures were performed at low temperature (i.e., cold room below 4°C). The resulting white paste was aged at 4°C for 24 hours to ensure homogeneous dispersion of the Pluronic hydrogel. Finally, the HAp ink was modeled at low temperature to obtain the desired 3D HAp scaffold, which was sintered at 1000°C for 2 hours using a muffle Carbolite ELF11 / 6B / 301. Hereafter, this product is denoted as s / x-HAp, where s means sintering and x corresponds to the mass percentage (%) of Pluronic hydrogel. For completeness, grains based on the prepared HAp powder were also prepared under the same temperature and time conditions (s-HAp).

[0126] 5.Catalyst activation The s-HAp disks, obtained by pressing 150 mg of s-HAp powder at 620 MPa for 10 min, and the s / x-HAp cubes were catalytically activated by placing the samples between two stainless steel plates (AISI 304) and applying a constant DC voltage of 500 V for 1 h while feeding GAMMA powder, keeping the temperature at 1000 °C. The samples were allowed to cool while maintaining the applied potential for 30 min, and finally, all systems were turned off and left to cool overnight. Hereafter, the catalysts obtained from s-HAp and s / x-HAp are referred to as HAp / c and x-HAp / c.

[0127] 6. Characterization The structure was analyzed using wide-angle X-ray diffraction (WAXD), Raman microscopy, scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) analysis. The water absorption capacity was obtained by contact angle measurement instrument.

[0128] More specifically, the structural analysis was performed using an inVia Qontor confocal Raman microscope (Renishaw) equipped with a Renishaw Centrus 2957T2 detector and a 532 nm laser. To obtain representative data, 32 single-point spectra were averaged.

[0129] Wide-angle X-ray scattering (WAXS) studies were performed using the Brucker D8 Advance model, Bragg-Brentano 2θ configuration, Cu K α The measurements were carried out using a one-dimensional Lynx Eye detector with a 2θ range of 20° to 60° in 0.02° increments and a scan rate of 2 s. The crystallinity (χ c ) was calculated using the following formula:

[0130]

number

[0131] In the formula, I 300 is the intensity of the (300) reflection, and V 112 / 300 is the intensity of the dip between the (112) and (300) reflections, which disappears in non-crystalline samples. The crystal size L hkl was calculated using the Debye-Scherrer equation.

[0132]

number

[0133] where λ is the wavelength of the monochromatic X-ray beam, B is the full width at half maximum of the peak of maximum intensity, and θ hkl is the peak diffraction angle that satisfies Bragg's law in the (hkl) plane.

[0134] SEM investigations were carried out using a focused ion beam Zeiss Neon40 microscope operating at 5 kV equipped with an EDX (20 kV) spectroscopy system. The latter technique was used to estimate the distribution composition of the ATMP / ZC / ATMP coatings.

[0135] The water absorption capacity was calculated using a contact angle measuring instrument OCA 15EC (Data-Physics Instruments). A 500 μL DS500 / GT glass syringe and needle SNS 021 / 011 were used for the ejection of the water droplet. The absorption flux was calculated by placing a 1.5 μL water droplet on the sample surface while recording with a camera at 30 fps. The photograms were then analyzed.

[0136] 7. Structural Characterization To achieve optimal catalytic activity, the as-prepared HAp powder was calcined at 1000 °C, followed by a dehydration process to increase the crystallinity, accumulate surface charges, and form OH - increased voids. Furthermore, exposure of the HAp ink at such high temperatures is also necessary to impart mechanical stability and remove the Pluronic hydrogel (which can inhibit catalytic performance and mask catalytic activity). In this section, the structure and crystallinity of s-HAp and s / x-HAp are compared with those of the as-prepared HAp pristine ones.

[0137] The WAXD spectra of the as-prepared HAp, s-HAp and s / 50-HAp samples are shown in Figure 1(a). All samples exhibited characteristic peaks of HAp at 2θ = 25.9°, 31.7°, 32.1°, 32.8°, 34.0°, and 39.8°, which correspond to the (002), (211), (112), (300), (202), and (310) reflections, respectively (JCPDS Card No. 9-0077). Representative crystallographic parameters (see Table 1 below) were obtained to determine whether the inhibition of Pluronic hydrogels affects the dehydration process.

[0138] [Table 1] Table 1. Representative crystallographic parameters obtained for the as-prepared HAp, s-HAp and s / 50-HAp samples.

[0139] In the two samples treated at high temperatures, the expected refinement of the crystallites was observed, and the crystallinity (χc ; Eq. S1) increased slightly from 0.78 ± 0.01 for HAp to 0.84 ± 0.02 for s / 50-HAp and 0.81 ± 0.02 for s-HAp. Nevertheless, the crystal size of the (211) main reflection (L 211 ), some structural differences emerged. A decrease of about 4 nm was observed for s / 50-HAp, suggesting that the presence of hydrogel limited the crystal growth in the crystal refinement process. This observation, together with the fact that the degree of crystallinity is higher in s / 50-HAp than in s-HAp, therefore indicates that the porosity promotes the formation of crystallization nuclei and thus the crystals are more numerous but slightly smaller in s / 50-HAp than in s-HAp. On the other hand, the intensities of the (002) and (112) reflections normalized by the intensity of the (211) main reflection (I 002 and I 112 ) is significantly lower in s / 50-HAp, supporting this hypothesis. 002 is commonly used to investigate the growth anisotropy through the c-axis of the HAp crystal lattice, which is also affected by the sintering of HAp grains (I 002 HAp >I 002 s-HAp >I 002 s / 50-HAp From these results, it can be concluded that the Pluronic hydrogel acts as a template to direct the shape and size of the HAp particles, resulting in porosity.

[0140] The formation of other calcium phosphate phases, such as β-tricalcium phosphate (β-TCP), could easily occur during the dehydration process. Although the characteristic reflection (021) at 2θ = 31.5° of β-TCP (JCPDS card no. 9-0432) was not observed in the WAXD spectrum, the formation of other salts was not completely ruled out, since most of the reflections of other salts share peak positions with HAp. Furthermore, Raman microscopy measurements were performed to obtain more detailed information on the phase distribution of the sintered samples.

[0141] The Raman spectrum shown in Fig. 1(b) shows the characteristic vibrational fingerprint of HAp (PO43- corresponding to an internal mode), it is possible to exclude the presence of Pluronic hydrogel residues (since no peaks related to Pluronic identity were detected) and other calcium phosphate salts. Thus, ν = 962 cm, which corresponds to the PO symmetric stretching mode. -1 The calcium phosphate salts were clearly identified by the characteristic splitting or shifting of the main peaks of ν1(A). Moreover, such peaks become sharper and more pronounced after sintering, indicating an increase in crystallinity. Furthermore, the ν1(A) peaks, which are related to the OH stretching mode, 3574 ) normalized by the area of ​​3574 cm -1 Evaluate the peak area of ​​OH during the dehydration process. - The appropriate generation of pores was controlled (Figure 1(c)). The results obtained were that for s-HAp, A 3574 = 0.160 ± 0.003, and for s / 50-HAp, A 3574 = 0.167 ± 0.002 is almost 33% lower than the value obtained for the as-prepared HAp, clearly indicating that the presence of Pluronic hydrogel does not affect the amount of voids finally formed. It can therefore be concluded that the sintering process was successful in suppressing hydrogel from the HAp scaffolds without affecting the final mineral composition.

[0142] 8. Effect of Pluronic Hydrogel on the Final HAp Scaffold Figure 2 compares SEM micrographs of s-HAp and s / x-HAp obtained with different Pluronic hydrogel mass percentages (i.e., 50%, 60%, 73%, and 78%). The generation of spherical nano- and sub-micrometer pores (120 ± 73 to 400 ± 122 nm) was clearly observed in all s / x-HAp samples. The nano- and sub-micrometer pores consistently showed a normal distribution in all samples (Figure 8), even though new groups of micrometer-scale cavities appeared when the Pluronic hydrogel mass percentage was increased from 50%, to 73% and 78% by weight (Figure 2). This phenomenon is believed to be the effect of residual hydrogel that was not properly dispersed in the HAp powder. Both types of pores independently coexisted, as their size was less dependent on the mass percentage of the Pluronic hydrogel (6.2 ± 2.0 μm for s / 73-HAp and 5.4 ± 2.8 μm for s / 78-HAp).

[0143] The porosity of the samples, related to nano- and sub-micrometer pores (i.e. excluding cavities in the micrometer range), was determined considering the percentage of void space observed in the SEM images and ranged from 6% to 14%. As shown in Figure 2 for s / 60-HAp, the high magnification images made it possible to identify how the Pluronic hydrogel droplets were the precursors of the resulting pores, favoring the arrangement of HAp sintered grains around them. Figure 3 shows that the pore size and porosity of s / x-HAp depend on the size and number of the hydrogel droplets, indicating that s / x-HAp can be controlled through the mass percentage of hydrogel added to the initial mixture.

[0144] The 3D printed HAp scaffolds were realized by extruding the Pluronic hydrogel-HAp mixture and showed a good rheological state because the hydrogel bonded with the HAp powder when kept at low temperatures (below 4 °C). Different HAp inks were preliminarily explored by varying the mass percentage of hydrogel to obtain optimal paste properties for 3D printing. Finally, a mass percentage of Pluronic hydrogel of about 60% was considered for further exploration due to its optimal printing properties, good mechanical stability, and control of pore size and porosity (see below). Figure 4(a)-Figure 4(b) show that such HAp ink was viscous enough to be introduced into a syringe, but dry enough to maintain the desired shape even at low temperatures where the Pluronic hydrogel was still liquid. Moreover, the sintered samples maintained the desired shape without showing any observable cracks or shrinkage, and showed good interfilament bonding and good structural stability (Figure 4(b)).

[0145] SEM images of the extruded filaments reveal a reduction in porosity at the exposed surface to 4% (Fig. 4c1), which is due to friction with the wall, suggesting that such behavior may be a drawback. However, when focusing on the fractured area of ​​the rod, where the interior (or cavity) is visible, the porosity recovers to a typical value of 12% (Fig. 4c2), which is consistent with what was observed for the s / 60-HAp sample (Fig. 3(b)). Although the surface porosity can be improved by precisely controlling the temperature and using a coated syringe and / or a more viscous HAp ink, our results show that the use of a syringe offers significant handling advantages.

[0146] Additionally, a water absorption study was conducted comparing s-HAp and s / 60-HAp scaffolds. To increase porosity, the s / 60-HAp scaffolds were made in a cubic shape (Figure 4(b)), whereas the s-HAp consisted of disks made by compressing HAp powder. Table 2 below shows that s / 60-HAp had almost four times more water flow absorption than s-HAp, which is mainly attributed to the pores of s / 60-HAp.

[0147] [Table 2] Table 2 Water absorption capacity of different samples before (s-HAp and s / 60-HAp) and after catalytic activation (HAp / c and 60-HAp / c)

[0148] The same investigations were carried out after catalytic activation of s-HAp and s / 60-HAp, which produced HAp / c and 60-HAp / c catalysts by application of the TSP process. The same experimental conditions (Methods section) were applied to both samples. Although the polarization process is known to affect the hydrophilicity of the samples due to surface charge induced effects (Rivas, M.; del Valle, LJ; Armelin, E.; Bertran, O.; Turon, P.; Puiggali, J.; Aleman, C. Hydroxyapatite with Permanent Electrical Polarization: Preparation, Characterization, and Response against Inorganic Adsorbates. ChemPhysChem 2018,19,1746-1755), an improvement in water uptake was only observed for HAp / c, which is attributed to the non-negligible effect of increased roughness. Despite this, 60-HAp / c exhibited a much better water uptake capacity (i.e., 1.5 times) than HAp / c, which is expected to promote the ultimate catalytic activity for carbon and nitrogen fixation reactions.

[0149] 9.60-Catalytic activity of HAp / c To clarify the effect of porosity on the catalytic activity of HAp-based catalysts, 60-HAp / c cubes were prepared and compared with HAp / c disks (Figure 5). For this purpose, s / 60-HAp cubes and s-HAp disks were poled using identical experimental conditions. The porosity was calculated in the previous section by examining SEM images of the grains and comparing different Pluronic hydrogel loadings. However, by utilizing certain geometrical parameters defined in Figure 5 instead of grains, the gravimetrically measured relative porosity (Π rel ), which seems more appropriate for comparing the two samples from a catalytic point of view. Thus: Π rel =1-ρ 60-HAp / c / ρ HAp / c (1) In the formula, ρ 60-HAp / c is the 60-HAp / c cube, ρ HAp / c is the density of the HAp / c disk, which was calculated using the parameters listed in Table 3 below. The resulting value, Π rel = 0.7 ± 0.03 indicates that the difference in porosity of the materials is larger than that determined by SEM examination. rel suggests higher porosity with good pore interconnectivity in the bulk, supporting the fact that external handling of the HAp ink results in a decrease in superficial porosity due to abrasion.

[0150] [Table 3] Table 3. Macroscopic parameters of 60-HAp / c and HAp / c catalysts (Figure 5). The exposed area considers only the surfaces of the geometric shape that are exposed in the reaction.

[0151] The catalytic performance of 60-HAp / c and HAp / c was compared for two different reactions based on nitrogen and carbon fixation: i) the production of ethanol using a mixture of CO2 and CH4 (Sans, J.; Revilla-Lopez, G.; Sanz, V.; Puiggali, J.; Turon, P.; Aleman, C. Permanently Polarized Hydroxyapatite for Selective Electrothermal Catalytic Conversion of Carbon Dioxide into Ethanol. Chem. Commun. 2021, 57, 5163-5166; and ii) the conversion of N2 to ammonia. As described below, the conversion of CO2 and CH4 to ethanol is improved by about 3000%, and the conversion of N2 to ammonia by about 2000%, compared to HAp / c.

[0152] 10. Fixation reactions of carbon and dinitrogen The catalyst was introduced into an inert reactor and two reported electrothermal catalytic reactions were tested: 1) the synthesis of ethanol from CO2 and CH4; and 2) the conversion of N2 to ammonia. Quantification of the reaction yields was performed using the 1 This was done using H-NMR spectroscopy, specific details of which are provided below.

[0153] The reactor was equipped with an inert reaction chamber coated with perfluorinated polymer (120 mL), into which both the catalyst and water (1 mL) were placed. The reactor was equipped with inlet valves for the inlet of N2, CH4, CO2 and an outlet valve to collect the gaseous reaction products. A UV lamp (GPH265T5L / 4, 253.7 nm) was also placed in the center of the reactor to directly irradiate the catalyst, the lamp was protected by a UV-transparent quartz tube. To avoid contact of the reaction medium with the reactor surfaces, all surfaces were coated with a thin film of perfluorinated polymer, thus eliminating other catalytic effects.

[0154] The reaction product is 1 All were analyzed by 1 H NMR spectroscopy. 1H NMR spectra were acquired using a Bruker Avance III-400 spectrometer operating at 400.1 MHz. Chemical shifts were calibrated using tetramethylsilane as an internal standard. 64 scans were recorded in all cases. To remove products formed on the catalyst from reactions involving CO2 and CH4, samples were dissolved in deuterated water containing 100 mM HCl and 50 mM NaCl, and finally deuterated water was added.

[0155] For the dinitrogen fixation reaction to produce ammonia, the catalyst (10 mg) was dissolved in 15 mL of water, the pH was adjusted to 2.1 ± 0.2 with 7.6 mM H2SO4, and NH4 + The conversion of ammonia in the bromine solution was accelerated by applying four cycles including ultrasonication (5 min) and stirring (1 min). 1 For H NMR sample preparation, 500 μL of the reacted catalyst solution was mixed with 100 μL of DMSO-d6 instead of a solvent containing unstable deuterons (i.e., DO) to avoid the formation of deuterated ammonium analogues, which are undesirable for quantitative analysis. The same treatment was applied to the aqueous supernatant.

[0156] 10.1 Ethanol production using CO2 and CH4 The performance of 60-HAp / c and HAp / c catalysts in ethanol production was compared. The reactions were carried out in the same reactor at 140 °C under CO2 and CH4 atmosphere (3 bar each), but without UV light for 48 h. Initially, the reactor was purged with CO2. The catalyst, HAp / c disk, or uncoated 60-HAp / c cube, and 1 mL of deionized water were taken into the reaction chamber (the reactions were carried out separately for each catalyst). Additionally, the effect of the initial water content on the reaction yield was investigated for one of the 60-HAp / c catalysts.

[0157] The ethanol yields obtained with both 60-HAp / c and HAp / c are compared in Figure 6(a). The amount of ethanol produced was about four times higher with 60-HAp / c than with HAp / c (55.0 ± 4.9 and 13.3 ± 0.7 μmol per g of catalyst, respectively), which means an outstanding increase in catalytic performance (414%).

[0158] Previous studies have demonstrated that while water is necessary as a proton source, excess moisture impedes gas immobilization on the HAp / c surface and reduces the final yield of the reaction (Sans, J.; Revilla-Lopez, G.; Sanz, V.; Puiggali, J.; Turon, P.; Aleman, C. Permanently Polarized Hydroxyapatite for Selective Electrothermal Catalytic Conversion of Carbon Dioxide into Ethanol. Chem. Commun. 2021, 57, 5163-5166). In this study, we investigated whether water content is still a limiting factor in 60-HAp / c, which is characterized by both pore generation and high water absorption compared to HAp / c. Therefore, a series of reactions were performed with initial water content varying from 1 to 80 mL while maintaining the CO2 and CH4 pressures (3 bar each), temperature (140 °C), and reaction time (48 h).

[0159] The ethanol yield, plotted in Figure 6(b), increased gradually with increasing initial water content, even though the initial water content introduced into the reactor was 80 times that used in the standard reaction of HAp / c (1 mL). This result explains the high potential of the 60-HAp / c catalyst, which can produce up to 434 ± 27 μmol per g of catalyst at a water content of 80 mL, reaching for the first time a production amount comparable to that reported for state-of-the-art Cu-based catalysts (Ma, W.; Xie, S.; Li.Xie, S.; Liu, T.; Fan, Q.; Ye, J.; Sun, F.; Jiang, Z.; Zhang, Q.; Cheng, J.; Wang, Y.Electrocatalytic Reduction of CO2 through Hydrogen-Assisted CC Coupling through Ethylene and Ethanol over Fluorine-Modified Copper. Nat. Catal. 2020, 3, 478-487). It is also noteworthy that no potential was required for the 60-HP / c performance, whereas Cu-based catalysts require the application of a potential. Meanwhile, zero ethanol or other products in the water left in the reactor was found, highlighting the catalyst's absorption capacity and highlighting its scalability. Overall, it can be concluded that porosity enhances the catalytic performance of HAp / c in ethanol production, obtaining for the first time yields high enough for industrial scalability and feasibility.

[0160] 10.2 Conversion of N2 to ammonia The production of ammonia over 60-HAp / c and HAp / c catalysts was carried out at 120 °C under UV irradiation. To remove the initial air content, the reaction chamber was first purged with N2 and then filled with N2 until a pressure of 6 bar was reached. A volume of 20 mL of deionized water was introduced into the reactor and contacted with the non-irradiated surface of the catalyst. It is noteworthy that in this reaction, water acted not only as a source of protons for ammonia production (by water decomposition) but also as a medium facilitating the recovery of the formed products. The products arising on the catalyst surface and those recovered in the liquid water after 24 h of reaction were: 1A procedure based on H NMR spectroscopy was applied to determine the + (Hodgetts, RY; Kiryutin, AS; Nichols, P.; Du, H.-. Bakker, JM; Macfarlane, DR; Simonov, AN Refining Universal Procedures for Ammonium Quantification via Rapid 1 H NMR Analysis for Dinitrogen Reduction Studies.ACS Energy Lett.2020,5,736-741).

[0161] The results shown in Figure 7 show that NH4 + The total amount of NH4 produced was 6.2 ± 0.9 μmol per gram of catalyst. + About 25% of the NH4 (i.e., 1.7±0.3 μmol per g of catalyst) remained adsorbed on the catalyst surface, while the majority of the reaction products were transferred from the catalyst to the aqueous medium (i.e., 4.5±0.6 μmol per g of catalyst). + The effect of porosity and water uptake capacity on the yield was dramatic, with the amount of product produced in the presence of 60-HAp / c increasing to 128.8 ± 22.3 μmol per g of catalyst. Moreover, the total yield, which showed an increase of more than 2000% over HAp / c, was recovered in the remaining liquid water. This feature is in full agreement with the results obtained in the previous reaction, confirming that 60-HAp / c promotes the synthesis of the reaction product.

[0162] By mixing HAp powder with Pluronic hydrogel, we successfully fabricated porous HAp scaffolds with controlled structure. The composition of this mixture allows the performance of the resulting ink to be tailored to meet the demands of 3D printing, and the appropriate mechanical stability is achieved by sintering at high temperatures. The sintered HAp scaffolds show high purity and crystallinity, reflecting a correct dehydration process. Thus, the addition of Pluronic hydrogel to enable a printable ink, and the subsequent generation of pores, does not affect the structure required for the preparation of polarized HAp-based catalysts.

[0163] The catalytic activity of the porous samples was evaluated using various carbon and / or dinitrogen fixation reactions. The 60-HAp / c catalyst showed a remarkable increase in the reaction yield, which is mainly attributed to the improved water uptake capacity and larger exposed surface. More specifically, the presence of microcavities inside the catalyst facilitates the heterogeneous catalytic process used in the production of ethanol and ammonia. Overall, due to its catalytic activity and enormous scalability potential, 60-HAp / c is considered as a solid, inexpensive, and environmentally friendly alternative to other conventional catalysts.

Claims

1. A porous permanently polarized hydroxyapatite, said porous permanently polarized hydroxyapatite having an average pore diameter of 10 nm to 500,000 nm.

2. 2. The porous permanently polarized hydroxyapatite according to claim 1, characterized in that the average pore diameter is between 10 nm and 10,000 nm, in particular between 50 nm and 1,000 nm, preferably between 60 nm and 600 nm, more preferably between 100 nm and 350 nm.

3. 3. The porous permanently polarized hydroxyapatite according to claim 1 or 2, characterized in that the porous permanently polarized hydroxyapatite has nanometer pores and submicrometer pores, or nanometer pores, submicrometer pores and micrometer pores.

4. the nanometric pores have an average pore diameter of 1 nm to 100 nm, in particular 10 nm to 90 nm, preferably 50 nm to 80 nm, and / or the submicrometer pores have an average pore diameter of 101 nm to 999 nm, in particular 120 nm to 900 nm, preferably 150 nm to 200 nm; and / or The micrometric pores have an average pore diameter of 1 μm to 500 μm, in particular 2 μm to 100 μm, preferably 5 μm to 10 μm 4. The porous permanently polarized hydroxyapatite according to claim 3.

5. - Wide angle X-ray scattering (WAXS) pattern shown in Figure 1(a) and / or - Raman spectrum shown in Figure 1(b) and / or - As shown in FIG. 31 P-NMR spectrum The porous permanently polarized hydroxyapatite according to any one of claims 1 to 4, characterized in that it has

6. A process for obtaining the porous permanently polarized hydroxyapatite according to any one of claims 1 to 5, comprising the steps of: (a) providing a mixture comprising or consisting of hydroxyapatite powder and a pore forming material; (b) shaping the mixture provided in step (a) to obtain a shaped body comprising or consisting of the hydroxyapatite powder and the pore-forming material; (c) sintering the body obtained in step (b) to remove the pore-forming material and obtain a body comprising or consisting of porous hydroxyapatite; (d) a constant or variable DC voltage, particularly between 250 V and 2550 V, or an equivalent electric field, particularly between 1.49 kV / cm and 15 kV / cm or, In particular, electrostatic discharges of 2500 V to 1500000 V, or equivalent electric fields of 148.9 kV / cm to 8928 kV / cm, applying a pressure to the molded body obtained in step (c) to obtain a molded body comprising or consisting of porous permanently polarized hydroxyapatite; (e) cooling the molded body obtained in the step (d) while maintaining the DC voltage or the equivalent electric field applied in the step (d); or, A step of cooling the molded body obtained in the step (d) while maintaining the electrostatic discharge or the equivalent electric field applied in the step (d); or, A step of cooling the molded body obtained in the step (d) without maintaining the DC voltage or the equivalent electric field applied in the step (d); or, cooling the molded body obtained in step (d) without maintaining the electrostatic discharge or the equivalent electric field applied in step (d); A process including.

7. 7. The process according to claim 6, characterized in that the pore-forming material comprises a polymer, in particular a polymer selected from the group consisting of poloxamers, polyolefins, polyesters, polyamides, polyimides, polyvinyl alcohols, polyurethanes, polycarbonates, polyalkyl terephthalates, polyaryl terephthalates, polyaryl ether ketones, polyhydroxyalkanoates, proteins, such as extracellular proteins and / or globular proteins and / or enzymes and / or antibodies and / or blood clotting factors, polysaccharides, and mixtures of at least two of said polymers.

8. The process according to any one of claims 9 to 11, characterized in that the polymer is a poloxamer.

9. 9. The process according to claim 7 or 8, characterized in that the poloxamer comprises a polyoxypropylene core with a molecular weight of 1 g / mol to 500,000 g / mol, in particular 1,000 g / mol to 30,000 g / mol, preferably 10,000 g / mol to 20,000 g / mol.

10. 10. The process according to any one of claims 7 to 9, characterized in that the poloxamer has a polyoxyethylene content of between 1% and 90% by weight, in particular between 10% and 80% by weight, preferably between 35% and 65% by weight.

11. 11. The process according to any one of claims 7 to 10, characterized in that the polymer has a proportion of from 1% to 90% by weight, preferably from 20% to 80% by weight, more preferably from 35% to 65% by weight, based on the total weight of the pore-forming material.

12. The process according to any one of claims 7 to 11, characterized in that the pore-forming material is in the form of a hydrogel.

13. A porous permanently polarized hydroxyapatite obtained or obtainable by a process according to any one of claims 6 to 12.

14. A composition or material, especially in the form of a catalyst, comprising a porous permanently polarized hydroxyapatite according to any one of claims 1 to 5 or 13.

15. Use of a porous permanently polarized hydroxyapatite according to any of claims 1 to 5 or 13, or a composition or material according to claim 14, as a catalyst, in particular in reactions for the synthesis of organic molecules, preferably ethanol, or inorganic molecules, preferably ammonia.

16. A composition, in particular a paste or ink composition, for preparing a porous permanently polarized hydroxyapatite according to any one of claims 1 to 5 or 13, comprising a hydroxyapatite powder and a pore-forming material.